The Heidelberg myth : the Nazification and Denazification of a German university - Remy, Steven P. (Harvard Univ. Press, 2002)
"In the first work to examine both the nazification and the denazification of a major German university, Steven Remy offers a sobering account of the German academic community from 1933 to 1957. Deeply researched in university archives, newly opened denazification records, occupation reports, and contemporary publications, The Heidelberg Myth starkly details how extensively the university's professors were engaged with National Socialism and how effectively they frustrated postwar efforts to ascertain the truth."--BOOK JACKET.